Digital Methods in the Humanities Challenges, Ideas, Perspectives - Schwandt, Silke (Digital Humanities Research, 2020)
Digital Humanities is a transformational endeavor that not only changes the perception, storage, and interpretation of information but also of research processes and questions. It also prompts new ways of interdisciplinary communication between humanities scholars and computer scientists. This volume offers a unique perspective on digital methods for and in the humanities. It comprises case studies from various fields to illustrate the challenge of matching existing textual research practices and digital tools. Problems and solutions with and for training tools as well as the adjustment of research practices are presented and discussed with an interdisciplinary focus.